We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
75
4
avatar

https://prnt.sc/p5weo9

 Sep 14, 2019

Best Answer 

 #1
avatar+609 
+1

\(2/5a+6 \begin{bmatrix} 3&\\ -2& \\7& \end{bmatrix} = \begin{bmatrix} 15& \\ -10 & \\35 \end{bmatrix}\)

we realize that the each element in the matrix was multiplied by 5 so a must be a value that will make 2/5a+6= 5 therefore a must be a negative reciprocal of 2/5 thus we will get -5/2 because that gives us -1 and when you add -1+6=5 which satisifes the equation. 

hope this helped. :) 

 Sep 14, 2019
 #1
avatar+609 
+1
Best Answer

\(2/5a+6 \begin{bmatrix} 3&\\ -2& \\7& \end{bmatrix} = \begin{bmatrix} 15& \\ -10 & \\35 \end{bmatrix}\)

we realize that the each element in the matrix was multiplied by 5 so a must be a value that will make 2/5a+6= 5 therefore a must be a negative reciprocal of 2/5 thus we will get -5/2 because that gives us -1 and when you add -1+6=5 which satisifes the equation. 

hope this helped. :) 

Nirvana Sep 14, 2019
 #2
avatar+609 
+1

also correct me if i am wrong.

Nirvana  Sep 14, 2019
 #3
avatar+104723 
+2

[(2/5)a + 6] * 3   = 15

 

(6/5)a + 18  =   15

 

(6/5)a  =  - 3

 

a  =   (-15/6)   =  (-5/2)

 

 

Check this in the other two  evaluations 

 

[ -1 + 6 ]  (-2)  =  [5] (-2)   =  -10

 

And

 

(-1 + 6 ] (7)  =  [5](7)  =  35

 

And Nirvava is correct  !!!!

 

 

 

cool cool cool

 Sep 14, 2019
 #4
avatar+609 
+1

yay!! :)) 

Nirvana  Sep 14, 2019

26 Online Users

avatar
avatar